Impact of Chlorella vulgaris powder on the nutritional content and preference of Khalas date spread - Ali, Rehab F. M.; El-Anany, Ayman M.; Almujaydil, Mona S.; Alhomaid, Raghad M.; Alharbi, Hend F.; Algheshairy, Reham M.; Alzunaidy, Nada A.; Alqaraawi, Seham S. (Frontiers in Nutrition, 2025)
IntroductionThe current study aimed to investigate the nutritional and sensory benefits of date fruit spreads formulated with Khalas date, olive oil, psyllium, roasted coffee, cocoa powder (CP), and incorporated with different quantities of Chlorella vulgaris powder (CVP).MethodsThe original spread consists of 65% Khalas dates, 30% Extra virgin olive oil (EVOO), and smaller amounts of psyllium, coffee, cocoa powder, and salt. By substituting EVOO with CVP in different proportions, the healthy spread formulas were produced.Results and discussionProtein content increases from 2.21% in control to 9.82% with 10% CVP. Ash content rises significantly with 10% CVP, with values up to 3.04 times higher than control. A 10% addition of CVP aligns the amino acid profile with FAO/WHO standards, except for lysine, which reaches 65.37% of the recommended levels. Additionally, the polyunsaturated fatty acid content increases substantially, with linoleic acid rising from 5.08% to 6.45% and linolenic acid from 0.7% to 2.75% at the 10% CVP level. DPPH radical scavenging activity, improves significantly, indicating the potential of CVP as a functional food ingredient. While lower concentrations of CVP (2-4%) do not significantly affect acceptability, higher concentrations (6-10%) lead to significant declines in consumer ratings.